PENGARUH STORE ATMOSPHERE DAN IN STORE PROMOTION TERHADAP PERILAKU IMPULSE BUYING - Bagaskara, Ardhito Katon; Ngatno, Ngatno (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2017)
These days, the development of retail business become very rapidly. In indonesia, Carrefour is one of large retailer on modern retail market share. Consumer behavior while shopping in modern retail can be influenced by several factors. The store atmosphere and in store promotion influence impulse buying behavior. Problems in this study there are still some several branches unable to meet predetermined sales goal. This happened in Semarang City. The result shows that the store atmosphere and in store promotion have positive impacts upon impulse buying behavior. It can be seen from the outcome of simple linier regression also t test. Store atmosphere has impact bigger towards the impulse buying behavior to consumers of Carrefour outlets in Semarang City, reaching the number 0.323, compared with in store promotion that only get 0.220. The coefficient of determination (R2) of lifestyle and price is 11.6%. This means 11.6% of impulse buying behavior can be explained by those two variables, while the other 88.4% by another variables.